Education and women in the early modern Hispanic world - Howe, Elizabeth Teresa, 1945- (Ashgate Pub. Co., 2008)
"Considering the presence and influence of educated women of letters in Spain and New Spain, this study looks at the life and work of early modern women who advocated by word or example for the education of women. The subjects of the book include not only such familiar figures as Sor Juana and Santa Teresa de Jesus, but also of less well known women of their time." "The author uses primary documents, published works, artwork, and critical sources drawn from history, literature, theatre, philosophy, women's studies, education, and science. Her analysis juxtaposes theories espoused by men and women of the period concerning the aptitude and appropriateness of educating women with the actual practices to be found in convents, schools, court, theaters, and homes. What emerges is a fuller picture of women's learning in the early modern period."--Provided by Publisher.
Keywords: Women -- Education -- Latin America -- History.; Women -- Education -- New Spain -- History.; Women -- Education -- Spain -- History.; Women -- Latin America -- Social conditions.; Women -- New Spain -- Social conditions.; Women -- Spain -- Social conditions.; Femmes -- Éducation -- Amérique latine -- Histoire.; Femmes -- Éducation -- Nouvelle-Espagne -- Histoire.; Femmes -- Éducation -- Espagne -- Histoire.; Femmes -- Amérique latine -- Conditions sociales.; Femmes -- Nouvelle-Espagne -- Conditions sociales.; Femmes -- Espagne -- Conditions sociales.; EDUCATION -- Organizations & Institutions.; Women -- Education; Women -- Social conditions; Latin America; New Spain; Spain; History